Inkjet‐Printed Metal‐Insulator‐Metal Capacitors for Tunable Microwave Applications. (30th November 2014) - Friederich, Andreas; Kohler, Christian; Nikfalazar, Mohammad; Wiens, Alex; Jakoby, Rolf; Bauer, Werner; Binder, Joachim R.
Abstract : A Ba0.6 Sr0.4 TiO3 –ZnO–B2 O3 composite ink was prepared and used for the manufacturing of fully inkjet‐printed metal‐insulator‐metal varactors. The dielectric thick films were co‐fired with printed silver electrodes at 850°C and show a fine grained microstructure. The films have a relative permittivity of εr = 129 and a dielectric loss of tan δ = 0.043 at f = 3 GHz. Printed varactors with different dielectric film thickness were prepared. The characterization of the printed structures and 3D electromagnetic simulations of the layout reveal the strong influence of electrode inductance and fringing effects on the properties of the components. The printed varactors reach tunabilities between 14.4% and 16.4% by applying a tuning field of 5 V/μm. To demonstrate the capability of the inkjet printing process for the preparation of tunable microwave devices, a fully inkjet‐printed phase shifter was fabricated. It is based on seven pairs of the printed varactors and reaches a phase shift of 180° and a figure of merit of 19°/dB at 3.4 GHz.